Media Pembelajaran Interaktif Untuk Pelajaran Geografi Kelas IX SMP dengan Macromedia Flash Pro 8 - Harjono (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2016)
One of the ways to deliver learning materials to students is through Instructional Media. By the using of the media, students may accept and understand the topic effortlessly. With the rapid development of technology and science, an interesting and easily understandable application is needed by the students to study the social sciences-especially, for the ninth grade Geography lessons- that aim to support the absorption process of learning materials. The base of this application construction is the using of action script programming language, combined with the animation created using Macromedia Flash Pro 8 applications are supported by Adobe Audition CS5.5.The data material taken from textbooks geography class IX in accordance with the applicable curriculum. This application contains the main and sub materials of teaching materials, evaluation questions along with assessment results of the evaluation, and reference sources of of teaching materials. To improve the attractiveness and for ease of understanding, teaching materials presented in the form of text, video and audio are packed into animations. GUI designed suitable to the characteristics of students of class IX. From the examination result, it can be concluded that the use of interactive learning media is capable to facilitate educators (teachers) to provide more effective and attractive learning delivery alternatives. It is expected to arouse the interest of students to learn Geography.